Institutional Organization as a Learning Process for Youth to Develop The Agricultural Education Tourism Village “Kampung Semai” - Kaulika, Vania Wilona; Zulkarnain, Zulkarnain; Sopingi, Sopingi (Universitas Negeri Malang, 2024)
Educational tourism refers to a type of travel designed to provide an educational experience to its participants. The goal of educational tourism is to incorporate elements of learning and education into the travel experience, so that participants not only have fun but also gain new knowledge and understanding. This research aims to determine the process of institutional organization at Eduwisata Kampung Semai. This can be seen from how they form institutions, coordinate local communities to participate, and how administrators carry out activities starting from tourism education planning to the final stage, namely evaluation. Overall, this research confirms that institutional organizing can be an effective tool for empowering youth and building healthy communities. Keywords : Organizing, Institutional, Agricultural Education